Cloud-based platforms for LoRa internet of things: a survey - Mouna Gassara; Manel Elleuchi; Mohamed Abid (International Journal of Informatics and Communication Technology (IJ-ICT), 2021)
Internet of Things (IoT) establishes a smart communication system between the human being and the surrounding objects (or “things”) while using the internet as the backbone of this system. Cloud is the fundamental constituent of IoT. It offers important application services in numerous application domains. Indeed, many IoT cloud platforms are competing to provide appropriate and very specific IoT services. The LoRa platform in particular presents a long-range, low-bit rate, low-power, wireless telecommunication protocol for IoT. As such, end-devices make use of LoRa through a sole wireless hop in order to communicate to the gateway(s) that is (are) considered as relay messages and transparent bridges between these end-devices and an IoT cloud while connecting to the Internet. This article surveys the most used IoT cloud platforms suitable for the LoRa communication protocol through a deep and detailed study of previously published works related to this topic. Moreover, a comparison is made between these IoT cloud platforms according to their characteristics and application domains. The overall aim of the present paper is to provide researchers in the field with detailed knowledge concerning the IoT cloud platforms appropriate to the LoRa communication system including the advantages and drawbacks of each one of them.